The effect of specific strength training on the quality of gymnastic elements execution in young gymnasts - Sawczyn, S.; Zasada, M.; Kochanowicz, A.; Niespodzinski, B.; Sawczyn, M.; Mishchenko, V. (Baltic Journal of Health and Physical Activity, 2016)
Background: The aim of the study was to determine the effect of specific gymnastics strength training on the quality of technical indicators of gymnastic elements in young gymnasts.